Other arts and adaptations - Kelly, M (Cambridge University Press, 2020)
Music, dance, film, and photography have been a consistent feature of J. M. Coetzee’s fiction. The importance of these ‘other arts’ has been reinforced by recent biographical and archive-based accounts of the author’s life and work, with further evidence of the creative energy given to possible and realized adaptations and collaborations with artists, composers, and film-makers. This chapter explores a selection of references to these other arts from across the Coetzee corpus, with particular attention to the representation of aesthetic experience, claims about the distinctive capacities of non-literary art forms, and the relationship of these other arts to writing, self-reflexivity, and the body. It concludes with a consideration of adaptations of the novels for film and opera.